2014
DOI: 10.1159/000369020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intraperitoneal Curcumin Instillation on Postoperative Peritoneal Adhesions

Abstract: Objective: The aim of this study was to determine the effect of curcumin on adhesion formation in a rat cecum abrasion model. Materials and Methods: Thirty Wistar rats were randomized into three groups; the control group received saline, the curcumin group received 10 mg/kg of curcumin after cecal abrasion, and in the sham group the abdominal wall was closed without any abrasion to the cecum. On day 15, adhesions were assessed blindly using a standardized scale, and histopathological samples were taken and exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…[1,2] Recently, new surgical techniques, mucosal barriers, and many therapeutic agents, including progesterone, curcumin, methylene blue, vitamin E, surfactants, and hyperbaric oxygen, have been developed in efforts to prevent adhesion, but the work continues. [1,[3][4][5][6] Cordycepin, an adenosine analogue initially isolated in China in 1964, has been demonstrated to have a variety of biological functions, and is used to treat various medical conditions. Cordycepin has fibrinolytic, anti-apoptotic, antioxidant, anti-inflammatory, antimicrobial, immunomodulatory, nephroprotective, and hepatoprotective effects.…”
mentioning
confidence: 99%
“…[1,2] Recently, new surgical techniques, mucosal barriers, and many therapeutic agents, including progesterone, curcumin, methylene blue, vitamin E, surfactants, and hyperbaric oxygen, have been developed in efforts to prevent adhesion, but the work continues. [1,[3][4][5][6] Cordycepin, an adenosine analogue initially isolated in China in 1964, has been demonstrated to have a variety of biological functions, and is used to treat various medical conditions. Cordycepin has fibrinolytic, anti-apoptotic, antioxidant, anti-inflammatory, antimicrobial, immunomodulatory, nephroprotective, and hepatoprotective effects.…”
mentioning
confidence: 99%
“…Futhermore, curcumin has also been shown to increase fibrinolytic activity and cell migration towards the wound area, which makes it possible to be safe and effective in the prevention of PAA [56]. It has shown that treatment with 10 mg/kg curcumin for 15 days can significantly prevent PAA [57]. However, further studies are needed to show the most suitable and effective dose of curcumin for PAA in clinics.…”
Section: Ligustrazinementioning
confidence: 99%
“…Recently, Au nanoparticles were synthesized employing curcumin (diferuloylmethane) as a reducing and stabilizing agent, which is a naturally occurring hydrophobic compound of the ginger family Zingiberaceae . Curcumin has multiple medical benefits including antioxidant, antiviral, antitumor, and skin and/or wound healing properties. It increases fibrinolytic and cell-migration response near the wound area thus upregulating the healing mechanism . Moreover, preclinical trials on animal models have revealed the chemopreventive, antineoplastic, and anti-inflammatory properties of curcumin .…”
Section: Introductionmentioning
confidence: 99%
“…It increases fibrinolytic and cell-migration response near the wound area thus upregulating the healing mechanism. 17 Moreover, preclinical trials on animal models have revealed the chemopreventive, antineoplastic, and anti-inflammatory properties of curcumin. 18 However, its use is limited because of poor absorption, low solubility (at physiological pH), and rapid metabolism.…”
Section: Introductionmentioning
confidence: 99%